2006
DOI: 10.1309/axyy-4ajt-mnw6-frmw
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Micropapillary Carcinoma of the Breast : Association of Pathologic Features With Lymph Node Metastasis

Abstract: Invasive micropapillary carcinoma (IMPC) of the breast is characterized by a high incidence of axillary lymph node metastasis. To investigate the relationship between pathologic features and lymph node metastasis, 51 cases of breast carcinoma with IMPC components were studied. Immunohistochemical analysis for vascular endothelial growth factor (VEGF)-C and VEGF receptor (VEGFR)-3 was performed, and lymphatic vessel density was measured. The main findings included a significantly increased number of positive ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
75
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 19 publications
11
75
0
1
Order By: Relevance
“…[7][8][9][10][11] In contrast, invasive micropapillary carcinoma has a high incidence of axillary lymph node metastasis and poor prognosis and the mechanism is still poorly understood. In our previous study, 4 we found that invasive micropapillary carcinoma rich in tumor infiltrating lymphocytes was associated with an increased incidence of lymph node metastasis and an increased number of positive lymph nodes per case. A similar adverse effect of tumor infiltrating lymphocytes was also reported in primary cutaneous melanoma.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…[7][8][9][10][11] In contrast, invasive micropapillary carcinoma has a high incidence of axillary lymph node metastasis and poor prognosis and the mechanism is still poorly understood. In our previous study, 4 we found that invasive micropapillary carcinoma rich in tumor infiltrating lymphocytes was associated with an increased incidence of lymph node metastasis and an increased number of positive lymph nodes per case. A similar adverse effect of tumor infiltrating lymphocytes was also reported in primary cutaneous melanoma.…”
Section: Discussionmentioning
confidence: 76%
“…3 Invasive micropapillary carcinoma of breast is composed of small clusters of tumor cells lying within clear stromal spaces and exhibits axillary lymph node metastasis with extraordinary frequency. In a previous study of 51 cases of invasive micropapillary carcinoma, 28 cases showed prominent tumor lymphocyte infiltration, 4 yet this group of patients presented with a significantly higher rate of lymph node metastasis than the group without or with scanty tumor lymphocyte infiltration. To explore the potential mechanisms to account for this apparent discordant finding, we compared the immunologic profile and activities of the tumor infiltrating lymphocytes of the 28 cases of invasive micropapillary carcinoma with those in a similar number of cases of medullary carcinoma.…”
mentioning
confidence: 66%
“…It seems reasonable, therefore, to hypothesize that MTDH could promote the invasion and lymph node metastasis of IMPC through EMT. In addition, the previous studies have demonstrated that there were many microvessel in IMPC [29] and the VEGF-C high expression was associated with lymph node metastasis of IMPC [30] . The significance of MTDH expression was in correlation with VEGF in triple-negative breast cancer [31] .…”
Section: Discussionmentioning
confidence: 99%
“…Guo ve arkadaşlarının yaptığı bir çalışmada İMPK hücrelerinin yeni lenfatik damar yapımını indükleyen vasküler endotelyal büyüme faktörü-C sentezi yaptığı ortaya konmuştur; yeni yapılan lenfatik damarların tümör invazyonuna daha duyarlı olduğu ve bu yolla lenf nodu metastazını kolaylaştırdığı düşünülmektedir (27). Lenfovasküler invazyon sıklığı, çeşitli çalışmalarda farklı bulunmuş olup %15-80 arasında değişmektedir (1,(6)(7)(8)(9)11,20).…”
Section: Memeni̇n İnvazi̇v Mi̇kropapi̇ller Karsi̇nomuunclassified